The natural rate of interest in emerging Asia: Long-term trends and the impact of crises - Kensuke Tanaka; Prasiwi Ibrahim; Sybrand Brekelmans (Asian Development Bank Institute (ADBI), 2021)
This paper studies the evolution of the natural interest rate in five Southeast Asian countries and considers the effect of economic shocks on the natural interest rate in these countries. The natural interest rate is the interest rate that would prevail in an economy in equilibrium and in the absence of frictions. As such, it is a useful tool for formulating monetary policy, as well as for guiding policy makers in formulating other forms of economic policy such as fiscal policy. In this paper, we estimate the natural interest rate for five Southeast Asian countries using a state-space model over a period ranging from the early 1990s to 2020. We also estimate the effect of the Asian financial crisis and global financial crisis on the natural interest rate using local projections. We find that the natural interest rate has tended to decrease in the countries of our sample since 1990, although in some countries the rate has increased again recently due to the tightening of US monetary policy. We also find that the natural interest rate has tended to decline since the Asian financial crisis and the global financial crisis. In light of the current economic downturn, this paper argues that Southeast Asian countries should implement policies aimed at enhancing productivity and boosting aggregate demand, such as increasing the natural rate of interest.
Keywords: E43; E31; E42; E52; E58; G18; O53; O23; 330; natural rate of interest; monetary policy; Southeast Asia; Asian financial crisis; global financial crisis; COVID-19